2022
DOI: 10.18203/2349-2902.isj20220316
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgical treatment of distal humerus fractures in adults in Cotonou

Abstract: Background: Fractures of the distal humerus represent 1.3% of fractures in Cotonou. Their treatment is often surgical. The aim of this work was to assess the results of their osteosynthesis in a disadvantaged environment.Methods: This retrospective study from 2001 to 2015 included 38 operated patients for distal humerus fracture with a minimum follow-up of 12 months. The average age was 33.6 years; the predominance was male (27 cases). The major etiology was traffic accidents (31 cases), According to the AO cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The sex ratio of our study population was 1.86, indicating a male predominance. Our results are similar to those of Chigblo et al [12] who found a gender ratio of 1.7. The same is true of Kardali et al [13] and Monk M. et al [3] who found gender ratios of 1.2 and 1.5 respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The sex ratio of our study population was 1.86, indicating a male predominance. Our results are similar to those of Chigblo et al [12] who found a gender ratio of 1.7. The same is true of Kardali et al [13] and Monk M. et al [3] who found gender ratios of 1.2 and 1.5 respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The long delay in admission could be explained by the usual itinerary in Benin of people injured on public roads in Cotonou, which is characterised by initial recourse to peripheral health establishments and more often to traditional therapists [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation